İstanbul Arkeoloji Müzesinde korunan Mezopotamya kazılarında bulunmuş M. Ö. I. bin yıllarına ait cam eserler - Atik, Şeniz
The Glass-Wares Found in Mesopotamian Excavations belonging to the First Millennium B.C. Kept in ?stanbul Archaeological Museums